High-efficiency 100-W Kerr-lens mode-locked Yb:YAG thin-disk oscillator - Chen, Hongshan; Yan, Lisong; Liu, Heyan; Hao, Jingjie; Yang, Tingting; Liu, Hongyu; Zhang, Jin; Li, Quanming; Wang, Hailin; Zhu, Guangzhi; Zhu, Xiao; Xuan, Hongwen; et al. (Frontiers in Physics, 2023)
We demonstrate a Kerr-lens mode-locked femtosecond Yb:YAG thin-disk oscillator and investigate the approach to increase the optical-to-optical efficiency based on the scheme of direct multiple passes of the laser beam through the thin-disk medium. With twelve passes through the thin disk, 266-fs pulses were delivered from the oscillator with an average power of 105.6 W at a repetition rate of 20 MHz. The corresponding optical-to-optical efficiency is 31.1%, which is, to the best of our knowledge, the highest efficiency of any mode-locked thin-disk oscillator with pulse duration below 300 fs. This demonstration paves the way to even more efficient mode-locked femtosecond thin-disk oscillators, and provides an excellent laser source for the applications such as nonlinear frequency conversion and high-precision industrial processing.